Relationship Between Vitamin D Level and DNA Fragmentation Index of Sperm in Men Referred to Omid Infertility Center in Hamadan-Iran: A Cross-Sectional Study - Mohamadnabi Holakouie Naini; Elahe Talebi Ghane; Shamim Pilehvari (Journal of Family and Reproductive Health)
Objective: Unfortunately, the prevalence of infertility in Iran and the world is increasing. There is limited research on the relationship between vitamin D and DNA fragmentation index (DFI). DFI is a measure of DNA damage in sperm cells and is used to evaluate male fertility. Some studies suggest that vitamin D may play a role in sperm health and fertility. Materials and methods: In this cross-sectional study, 789 eligible men referred to the Omid Infertility Clinic in Hamadan-Iran in 2021-2023. Serum levels of vitamin D, DFI, spermogram indexes and demographic characteristics (occupation, age, and body mass index) were collected by face-to-face interview and records review in case files. Data were analyzed with SPSS version 27 software. Results: There is no significant relationship between DFI and vitamin D before and after removing the effect of confounding variables. Clearly, increasing age has been associated with increasing (DFI 95% Cl: 1.06-3.03; p<0.05) odds ratio (OR) = 1.79. The relationship between the increase in DFI and the decrease in normal sperm morphology (95% CI: 1.43-4.20; p<0.01) OR = 2.45 and the decrease in the progressive motility of sperm was seen (95% Cl: 1.66-4.87; p<0.05) OR= 2.85 and also. The relationship between DFI and the decrease in sperm count after removing the effect Confounding variables were observed (95%Cl: 1.06-8.38; p<0.05) OR=2.98. Conclusion: No correlation between DFI and vitamin D serum level was found. However, a clear association was observed between increased DFI and advanced age, reduced progressive motility, abnormal sperm morphology, and decreased sperm count.